Investigation of Moringa Leaf Compounds as Colon Anticancer Agents Using Bioinformatics and Molecular Docking Methods - Saputri, Dwi; Kusumaningtyas, Triana; Setiadi, Prismo; Febriansah, Rifki (Universitas Muhammadiyah Yogyakarta, 2023)
Introduction - Colon cancer is a disease that has a high mortality rate. Cancer treatments such as chemotherapy can cause severe side effects. So, it is necessary to do research on herbal plants to minimize these side effects. The bioactive compounds in Moringa leaves (Moringa oleifera L.) are known to have antioxidant and anticancer activity, so they have the potential to be used as cancer treatment. Purpose – . This study aims to determine the potential of Moringa leaves as an anticancer agent in silico. Methodology/Approach – The in silico test used is STITCH-STRING bioinformatics and molecular docking. STITCH-STRING bioinformatics was used to determine the target protein of the test compound, and molecular docking was used to determine the binding affinity between the test compound and cancer protein. Findings – In the STITCH-STRING bioinformatics test, the potential targets for kaempferol and quercetin were TP53-ESR1 and STAT3-EGFR, respectively.test Molecular docking on cancer protein showed that quercetin compound in EGFR protein had the best binding with a docking score of -9.2 kcal/mol. This shows good results because the docking score obtained is lower than the comparison drug (Fluorouracil) which has a docking score of -4.2 kcal/mol. These results indicate that compounds in Moringa leaves (Moringa oleifera L.) have the potential to be used as anticancer agents. Originality/ Value/ Implication – Moringa leaf research using bioinformatics and molecular docking methods is still rarely done, so this research can be used as further knowledge related to the search for moringa leaf compounds that have the potential for anticancer using bioinformatics and molecular docking methods